SHAHEEN, JACK G. REEL BAD ARABS: HOW HOLLYWOOD VILIFIES A PEOPLE. MASSACHUSETTS: OLIVE BRANCH PRESS, 2015. - SANTOS, Andrey Augusto Ribeiro dos (Tempos Históricos, 2018)
SHAHEEN, JACK G. REEL BAD ARABS: HOW HOLLYWOOD VILIFIES A PEOPLE. MASSACHUSETTS: OLIVE BRANCH PRESS, 2015.